Modified Iliac Screw in Lumbopelvic Fixation After Sacral Tumor Resection: A Single-Center Case Series. Issue 4 (2nd April 2023) - Huang, Wending; Cai, Weiluo; Cheng, Mo; Hu, Xianglin; Fang, Meng; Sun, Zhengwang; Wang, Shengping; Yan, Wangjun
Abstract : BACKGROUND: Traditional iliac screw, S2-alar iliac screw, and modified iliac screw are the 3 common techniques for lumbopelvic fixation. The application of the modified iliac technique in sacral spinal tumors has been rarely reported. OBJECTIVE: To report the feasibility and safety of modified iliac screws after sacral tumor resection and their preliminary clinical outcomes. METHODS: Twenty-seven patients who underwent sacral tumor resection with modified iliac screw fixation between August 2017 and August 2021 at our center were clinically and radiographically evaluated. RESULTS: A total of 59 iliac screws were inserted by freehand according to the anatomic landmarks. The mean operation time was 207 minutes (range, 140-435 minutes). The average estimated blood loss was 1396 mL (300-4200 mL). Computed tomography scans showed that 2 (3.4%) screws penetrated the iliac cortex, indicating a 96.6% implantation accuracy rate. There were no iatrogenic neurovascular or visceral structure complications observed. The mean minimal distances from the screw head to the skin were 24.9 and 25.8 mm on the left and right sides, respectively. The mean minimal distances from the screw head to the horizontal level of the posterior superior iliac spine were 7.9 and 8.3 mm on the left and right sides, respectively. Two patients (7.4%) underwent reoperation for wound infection. At the latest follow-up, no patient had complications of screw head prominence, pseudarthrosis, or instrument failure. CONCLUSION: The modified iliac screw is characterized by its minimal invasiveness and simplicity of placement. It is an ideal alternative for lumbopelvic fixation after sacral tumor resection.